2021
DOI: 10.1371/journal.pone.0259317
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication practices to prevent or manage COVID-19: A systematic review

Abstract: Background Previous studies have assessed the prevalence and characteristics of self-medication in COVID-19. However, no systematic review has summarized their findings. Objective We conducted a systematic review to assess the prevalence of self-medication to prevent or manage COVID-19. Methods We used different keywords and searched studies published in PubMed, Scopus, Web of Science, Embase, two preprint repositories, Google, and Google Scholar. We included studies that reported original data and assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
77
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 40 publications
5
77
0
1
Order By: Relevance
“…HCQ was used in only 1.3% unlike that reported in this present study where 34.3% of respondents used HCQ. This is not surprising as the respondents in our study were all health care workers unlike the study population in the study by Wegbom et al 25 Similar to our study Sadio et al 17,32 also reported Vitamin C, HCQ and Azithromycin amongst the drugs most commonly used. However, 10.2% of their respondents also used traditional medication.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…HCQ was used in only 1.3% unlike that reported in this present study where 34.3% of respondents used HCQ. This is not surprising as the respondents in our study were all health care workers unlike the study population in the study by Wegbom et al 25 Similar to our study Sadio et al 17,32 also reported Vitamin C, HCQ and Azithromycin amongst the drugs most commonly used. However, 10.2% of their respondents also used traditional medication.…”
Section: Discussionsupporting
confidence: 82%
“…28,29,30 Our study showed the top 5 medications used by health workers were tabs Vitamin C, Zinc, Azithromycin, antimalarials (other than Hydroxychloroquine) and Hydroxychloroquine (HCQ). Similarly, Wegbom et al 25,32 reported Vitamin C and antimalarials other than HCQ as being amongst the top 5 drugs used for SM. However, they reported their respondents also used antibiotics like amoxicillin and ciprofloxacin and herbal products commonly.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“… 59 One of the challenges identified in the COVID-19 era has been the use of antimicrobials as self-medication agents, such as ivermectin, azithromycin, doxycycline, and hydroxychloroquine, which might predispose to toxicity and resistance development. 44 , 66 , 77–80 Medications for the prevention of COVID-19 are mainly vitamins 15 , 66 , 79 , 81 and zinc. 81 Integrated public health education at the community level has an indispensable role in increasing awareness and decreasing the burden on facility-based health-care delivery, and efforts should be made to help mitigate risks of self-medication by the active involvement of pharmacists and other members of the health-care team to correct false claims about drugs.…”
Section: Discussionmentioning
confidence: 99%